Currency Crises in Developed and Emerging Market Economies : A Comparative Empirical Treatment - Fontaine, Thomson (IMF Working Papers; Working Paper ;, 2005)
This paper takes a step in empirically testing the implications of a number of theoretical models that attempt to highlight the dynamics behind currency crises. By focusing on countries with broadly disparate economic and political arrangements, the study attempts to determine the extent to which these variables matter in affecting the probabilities of currency crises occurring. The empirical findings provide support for the view that, in general, a deterioration in economic fundamentals and the pursuit of lax monetary policy can contribute to currency crises. The experiences of several emerging market economies suggests that the sustainability of exchange rate policy depends both on adequate policy responses to the shocks to the economy and on the fragility of the economic, financial, and political system.